The Application of KUB for Detecting of Submucosal Ureteral Stones - Aghamir, Seyed Mohammad Kazem; Mohseni, Mohammad Ghasem; Ardastani, Arash (Urology Journal, 2009)
Purpose: The accurate diagnosis of submucosal ureteral stones in order to choose a proper and less complicative method of treatment is of significant importance. The use of KUB to detect submucosal ureteral stones has been studied in this research. Materials and Methods: This prospective study has been carried out on 33 patients (23 males and 10 females) with lower ureteral stone (17 cases in the right ureter and 16 in the left) located under iscial spine as was indicated in their KUB. The distance from the lower end of stone to the midline of sacrum was measured per millimeter using KUB. All patients underwent ureteroscopy, and accordingly those with submucosal ureteral stones were distinguished. The correlation between the distance of the lower end of stone from the middle line of sacrum and the existence of submucosal ureteral stone was analyzed. Results: Nineteen out of 33 studied patients had submucosal ureteral stones. The average distance between the peak of stone and the middle line of sacrum in patients with submucosal ureteral stone was 9.7 mm with an accuracy of 1.4 mm, a confidence interval 95% and standard deviation of 3.1 mm. Accordingly, if the distance of stone from the middle line of sacrum is lower than 13.7 mm, in 90% of cases the stone will be submucosal. Conclusion: In patients with lower ureteral stone, the KUB of whom indicates a stone under iscial spine, if the distance of the peak of stone from the midline of sacrum was lower than 15 mm, the stone could most likely be submucousal, a point, which should be considered during treatment. In such cases the intravesical approach should be considered intraoperatively and preparation for submucosal ureteral incision must be provided. This method would be useful in stone removal, if the classic ureteroscopy was not successful.